PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF GAMIFIKASI “GEMA” UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI KELAS V - Sudrajat; Aura Maulida Rachma; Nindy Mardani (Universitas Muhammadiyah Metro, 2025)
In response to the rapid advancements in education, teachers face the challenge of designing engaging and meaningful learning experiences. Mathematics, often perceived as a difficult subject due to its computational nature, remains a particular area of concern. Preliminary observations indicate that elementary mathematics instruction frequently relies on conventional methods, lacking innovative approaches, which results in low student engagement and participation. This study aims to enhance mathematics learning outcomes on the topic of plane figure perimeter among fifth-grade students at SDN 3 Sumber by implementing “GEMA